Influence of Fasting or Early Feeding on Broiler Performance - El -Husseiny, O.M.; El-Wafa, S. Abou; El-Komy, H.M.A. (International Journal of Poultry Science, 2008)
Three experiments were designed to investigate the effect of early feeding on yolk sac absorption and enhance the gastrointestinal tract development in neonatal broiler chicks. Experiment I, was designed to answer the question about the extent of yolk sac absorption and survivability in newly hatched chicks with held feed (for 1, 2, 3, 4, 5 or 6 days then switch to control diet), but have access to water. Two hundred and eighty unsexed day-old Arbor Acres broiler chicks were divided equally into 7 treatments of 40 chicks each in four replicates (10 chicks each). Diets were formulated to contain 23% CP and 3200 Kcal ME/kg (Starter) and 20% CP and 3200 Kcal ME/kg (grower). Experiment II, was designed to answer the question about the feed utilization, yolk sac absorption and gastrointestinal tract maturation in newly hatched chicks when fed different treatments ( ground yellow corn, soybean meal flour, yolk sac, fresh egg yolk, low protein diet and control diet) for two days then switched to control diet A total number of 240 unsexed day old, Arbor Acres broiler chicks was randomly assigned to 6 treatments of 40 chicks each in four replicates (10 chick per replicate). Exp. III, was designed to answer the question about supplementation of some nutrients in water (glucose, amino acid (Meth and Lys), amino vit, electrolyte and tap water) and effects on yolk sac absorption and gastrointestinal tract maturation in newly hatched chicks. A Total number of 360 unsexed day old, Arbor Acres broiler chicks were randomly assigned to 9 treatments of 40 chicks each in four replicates (10 chicks per replicate). Results obtained are as follows: Yolk was rapidly utilized in fed than in fasting chicks at 1st and 2nd days of age. However, the lowest CP% of yolk sac was recorded at 4th day of fasting and better absorption of nutrients from yolk sac after 72h of life was observed in group fasting compared with the group which was fed. Moreover, Starvation over the first 2-d post-hatch period retards growth, reduces ultimate meat yield and weight loss after 5 day starvation resulted in completely death of all chicks. Starvation in the early period (0-7d) significantly (P